(untitled) (Khairulummah, 2023)
Islam is a religion of justice, equality, and fairness, and its teachings are based on ease, moderation, tolerance, and the removal of embarrassment. Its provisions are general to all eras and regions, and include all sectors of human life, whether religious, devotional, social, political, economic, international, and other life activities that abound in societies. Based on the principle of generality and eternity in this Hanafi law, which is binding on those who are responsible, and based on the rule of justice and equality, which is considered one of the most important and solid rules of Islamic society, the minorities that have agreed to live under the Islamic state, which does not treat anyone unfairly, and only leads to the happiness of all.